Effect of Rebranding and Product Quality on Brand Image at Extracurricular PT. One Roof Surabaya - fajarani, bestari; Susilowati, Luky (Jurnal Ekonomi Balance, 2022)
At present, Indonesia has various industrial sectors ranging from technology, fashion, design, culinary, competing with each other to show their existence in the business world, so that companies are able to survive with competitors, namely by continuing to innovate and create good quality products. Brand Image is very important so that people are more familiar with a product. Brand image and product quality are used by companies in order to create product brand images in the minds of consumers. The population in this study are consumers who visit and enjoy food and beverage offerings at the One-Stop EXKUL in 2020. The sampling method used is random sampling/probability sampling using the Slovin formula. The samples taken were 100 respondents. The data used are primary data and secondary data. While the analysis technique used in this study is Particle Least Square (PLS). Based on the research results, it can be seen that Brand Image and Product Quality have a positive and significant effect on the Brand Image of EXKUL One Roof Surabaya